Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2174/187152709788921654
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sleep-Wake Cycle Modulation

Abstract: Regulation of the sleep-waking cycle is complex, involving multiple neurological circuits and diverse endogenous molecules. Interplay among assorted neuroanatomical and neurochemical systems such as acetylcholine, dopamine, noradrenaline, serotonin, histamine, and hypocretin maintain the waking (W) state. The sleep-onset is governed by the interacting forces of the sleep drive, which steadily increases with duration of W, and circadian fluctuations. Sleep-promoting neurons located in the anterior hypothalamus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 107 publications
0
42
0
1
Order By: Relevance
“…Since the neurotoxic effects of MDMA are diffuse and involve 5-HT neurons in both cortical and subcortical brain regions, it is not possible to precisely identify a mechanism by which brain 5-HT neurotoxicity might lead to the current findings. 5-HT also modulates sleep processes (Murillo-Rodriguez et al 2009), and sleep disruption is known to lead to changes in pain processing (Smith et al 2007;Edwards et al 2008;Tiede et al 2010). The current MDMA cohort had altered sleep architecture (i.e., decreased Stage 2 sleep) and pain measures in all subjects were significantly related to numerous sleep indices.…”
Section: Discussionmentioning
confidence: 87%
“…Since the neurotoxic effects of MDMA are diffuse and involve 5-HT neurons in both cortical and subcortical brain regions, it is not possible to precisely identify a mechanism by which brain 5-HT neurotoxicity might lead to the current findings. 5-HT also modulates sleep processes (Murillo-Rodriguez et al 2009), and sleep disruption is known to lead to changes in pain processing (Smith et al 2007;Edwards et al 2008;Tiede et al 2010). The current MDMA cohort had altered sleep architecture (i.e., decreased Stage 2 sleep) and pain measures in all subjects were significantly related to numerous sleep indices.…”
Section: Discussionmentioning
confidence: 87%
“…Дофамин -один из основных ней-ромедиаторов, обеспечивающих поддержание бодр-ствования [82]. Дофаминергические нейроны прое-цируются на различные структуры, участвующие в регуляции сна и бодрствования, включая дорсаль-ное ядро шва, голубоватое пятно, ядра гипоталаму-са, базальные отделы переднего мозга и таламус.…”
Section: патогенез первичной дс при бпunclassified
“…Actually, fibromyalgia patients prevalently experience unrefreshed sleep, which is involved as one of factors in the new fibromyalgia criteria (Wolfe et al, 2010). Because dopamine, norepinephrine, and serotonin in brain neurological circuits are considered to play an important role in the regulation of complex sleep-waking cycle (Murillo-Rodríguez et al, 2009), depletion of brain biogenic amines by reserpine may cause a disturbance of sleep-waking cycle in addition to the hyperalgesia. Actually, it has been reported that reserpine treatment significantly affects the sleep cycle including rapid eye movement (REM) sleep and slow-wave sleep (Hoffman & Domino, 1969).…”
Section: Face Validitymentioning
confidence: 99%